Perceptions of Children from Rio de Janeiro about Racial Representation: Notes from the Field (Novos Olhares, 2016)
This paper aims to start an analysis of children’s reaction to the dominance of positive White representation in the media. Through the usage of the concept of racial discrimination as a cultural trauma and the work of various authors on colorism in Brazil, there is a contextualization of children’s symbolically violent discourses in the schools.  The article also points out some strategies of discourse building and policies that are beginning to be made in an attempt to address this matter. The work is part of my Master’s research about the violence in children’s daily interactions, for which I have done fieldwork in two school of different social and economical profiles in the city of Rio de Janeiro.